(3cfR GdYQaGf aj abg GdbQGfs - (3ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf Hf eMeO GdSjhQj GdMdj GdCSOj,J (B826 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd Ydi YHOg GdcJGH dcd TF JHjGfkG CeG HYO aEf GdbQGf HMQ dGJZfi YLGFHg hdL dGjfbVi ZQGFHg s
(3BNQgG (B:s
( (3jG CjgG GdPjf CefhG chfhG bhGejf ddg TgOGA HGdbSW hdGjMQefce TjFGf bhe Ydi Cf dGJYOdhG EYOdhG gh CbQH dJbhe hGJbhG Gddg Ef Gddg NjQ HeG JYedhf (B) (3hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B282 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B318s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1517s
Keywords: (3GdJaSjQ hYdhe GdbQBfs